2022
DOI: 10.1186/s13072-022-00438-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple distinct domains of human XIST are required to coordinate gene silencing and subsequent heterochromatin formation

Abstract: Background Mammalian dosage compensation is achieved by the inactivation of one X chromosome in XX individuals. In eutheria this process is initiated early in development by the long non-coding RNA XIST. Studies of the initiation of silencing by XIST have focussed on mouse models, so the domains of XIST required to induce silencing in humans, and their relationship with domains required to establish heterochromatin remain to be determined. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Induction of an XIST cDNA integrated into an FRT site on chromosome 8p results in both silencing of flanking 8p genes and recruitment of heterochromatin marks ( 43 ). Assessment of deletions spanning this full XIST reinforced that the 5′ end of XIST including the conserved A repeats was critical for silencing ( 44 ). Although the 5′ A repeats are essential for silencing, they are only sufficient to induce local silencing ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Induction of an XIST cDNA integrated into an FRT site on chromosome 8p results in both silencing of flanking 8p genes and recruitment of heterochromatin marks ( 43 ). Assessment of deletions spanning this full XIST reinforced that the 5′ end of XIST including the conserved A repeats was critical for silencing ( 44 ). Although the 5′ A repeats are essential for silencing, they are only sufficient to induce local silencing ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, on the basis of the current knowledge about the different functions of each XIST domain, we tried to generate a smaller transgene that could recapitulate all XIST functions. Domain A is crucial for silencing by recruiting proteins at the initiation of XCI in both mice and humans ( 5 , 6 , 15 , 44 ), and domain E is implicated in XIST/Xist localization, also through protein interactions ( 12 , 28 , 29 , 48 ); however, our recent results suggested that the functional pathways utilized in human somatic cells may differ from those described in mouse differentiation [reviewed in Patrat et al. ( 7 )].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to stochasticity, genetic effects can influence the choice of allelic inactivation and contribute to population variability in XCI ratios. Allelic inactivation during XCI is mediated by the cis-acting long non-coding RNA XIST 30 , which silences its corresponding X-allele through epigenetic modifications 31,32 . Heterozygous variants affecting XIST expression can bias allelic inactivation 15 .…”
Section: Introductionmentioning
confidence: 99%